Cannabigerol modulates α2-adrenoceptor and 5-HT1A receptor-mediated electrophysiological effects on dorsal raphe nucleus and locus coeruleus neurons and anxiety behavior in rat - Mendiguren, Aitziber; Aostri, Erik; Rodilla, Irati; Pujana, Iker; Noskova, Ekaterina; Pineda, Joseba (Frontiers in Pharmacology, 2023)
The pharmacological profile of cannabigerol (CBG), which acid form constitutes the main precursor of the most abundant cannabinoids, has been scarcely studied. It has been reported to target α2-adrenoceptor and 5-HT1A receptor. The locus coeruleus (LC) and the dorsal raphe nucleus (DRN) are the main serotonergic (5-HT) and noradrenergic (NA) areas in the rat brain, respectively. We aimed to study the effect of CBG on the firing rate of LC NA cells and DRN 5-HT cells and on α2-adrenergic and 5-HT1A autoreceptors by electrophysiological techniques in male Sprague-Dawley rat brain slices. The effect of CBG on the novelty-suppressed feeding test (NSFT) and the elevated plus maze test (EPMT) and the involvement of the 5-HT1A receptor was also studied. CBG (30 µM, 10 min) slightly changed the firing rate of NA cells but failed to alter the inhibitory effect of NA (1-100 µM). However, in the presence of CBG the inhibitory effect of the selective α2-adrenoceptor agonist UK14304 (10 nM) was decreased. Perfusion with CBG (30 µM, 10 min) did not change the firing rate of DRN 5-HT cells or the inhibitory effect of 5-HT (100 µM, 1 min) but it reduced the inhibitory effect of ipsapirone (100 nM). CBG failed to reverse ipsapirone-induced inhibition whereas perfusion with the 5-HT1A receptor antagonist WAY100635 (30 nM) completely restored the firing rate of DRN 5-HT cells. In the EPMT, CBG (10 mg/kg, i.p.) significantly increased the percentage of time the rats spent on the open arms and the number of head-dipping but it reduced the anxiety index. In the NSFT, CBG decreased the time latency to eat in the novel environment but it did not alter home-cage consumption. The effect of CBG on the reduction of latency to feed was prevented by pretreatment with WAY100635 (1 mg/kg, i.p.). In conclusion, CBG hinders the inhibitory effect produced by selective α2-adrenoceptor and 5-HT1A receptor agonists on the firing rate of NA-LC and 5-HT-DRN neurons by a yet unknown indirect mechanism in rat brain slices and produces anxiolytic-like effects through 5-HT1A receptor.